The Implementation of Instructional Media in Teaching English to Young Learners - Petina, Fetin (Fakultas Keguruan dan Ilmu Pendidikan Universitas Pakuan, 2023)
This research aims to describe the implementation of instructional media in teaching English to young learners. Types of media are used during the learning process. This research is focused on the implementation of instructional media in teaching English to young learners. In this study, the writer applied qualitative descriptive method. To collect the data, the writer employed observation, documentation, and interview with the teacher. The participants in this study were students of grades 6B, 6C, and an English teacher at MIT MA Mathla'ul Anwar. The result of this research shows that the teacher uses different instructional media at each meeting. The teacher uses three types of instructional media in teaching English. These media are included in the types of print media (textbook), audio, and audio-visual media. Teacher sometimes insert the games that support instructional media in learning activities. The most effective instructional media used are smartphones and infocus. The use of instructional media applied to young learners can make learning interactive, creative, and communicative.